Privacy in Statistical Databases UNESCO Chair in Data Privacy International Conference, PSD 2008, Istanbul, Turkey, September 24-26, 2008, Proceedings - Domingo-Ferrer, Josep.; Domingo-Ferrer, Josep.; Saygin, Yücel.; Saygin, Yücel. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2008)
This book constitutes the refereed proceedings of the International Conference on Privacy in Statistical Databases, PSD 2008, held in September 2008 in Istanbul, Turkey, under the sponsorship of the UNESCO chair in Data Privacy. The 27 revised full papers presented were carefully reviewed and selected from 37 submissions. The papers are organized in topical sections on tabular data protection; microdata protection; online databases and remote access; privacy-preserving data mining and private information retrieval; and legal issues.